Perbandingan Kemampuan Menulis Permulaan Siswa Kelas 1 SD Negeri 004 Batu Ampar Berdasarkan Siswa Tamatan TK dan Tidak Tamatan TK - Deantika Prawita Putri; Otang Kurniaman; Neni Hermita (el-Ibtidaiy:Journal of Primary Education, 2021)
this research is intended to describe the starting skiills of students class 1 SD Negeri 004 of Batu Ampar, based on kindergarten students and non-kindergarten students. The subject of this was 20 students class 1 SD Negeri 004 of Batu Ampar stone made up of 10 students who graduated from kindergarten and 10 those students who didn’t graduate from kindergarten. The method employed in the study is a quatitative descriptive method and dating-collection instrument consisting of tests consisting of 20 short written tests, which divide into four types of the vait: thicking letters, thicking words, copying words and copying sentences. The data obtained is further analyzed using a descriptive statistical technique. Studies suggest that there is a differenc betwen the ability to write an undergraduate students. In wich one woul have been a hundred times better writing ability for kindergarten students than avarage grades for kindergarten students 86,1%  in “very good” and students didn’t kindergarten are 74,2%  in category “good”.